Empirical assessment of equity and justice in climate adaptation literature: a systematic map. (23rd June 2021) - Coggins, Shaugn; Berrang-Ford, Lea; Hyams, Keith; Satyal, Poshendra; Ford, James; Paavola, Jouni; Arotoma-Rojas, Ingrid; Harper, Sherilee
Abstract: The normative concepts of equity and justice are rising narratives within global climate change discourse. Despite growing considerations of climate equity and justice within the adaptation literature, the extent to which adaptation research has worked to empirically assess and operationalize concepts of equity and justice in practice remains unclear. We employ a systematic mapping approach to examine how equity and justice are defined and understood within empirical climate change adaptation research, and how extensively they are being assessed within adaptation literature. Structuring our work using a conceptual approach focusing on distributional, recognition, procedural, and capability approaches to justice, we document and review articles that included empirical assessments from searches performed in Web of Science™, Scopus®, and Google Scholar™ databases. Our results highlight that greater attention in the literature is given to certain aspects of justice (e.g. distributive and procedural justice concerns) on certain topics such as climate policy and adaptation finance. Most of the included papers scored highly according to our criteria on their empirical assessment of equity and justice. The lowest scores were found for the methodological rigor of assessments. We find limited research on empirical equity and justice assessment and call for a multiscale and holistic approach to justice to address this research gap.